RETRO-AORTIC LEFT RENAL VEIN AS A CAUSE OF UNILATERAL DENSE PERSISTENT NEPHROGRAM: Unilateral Dense Persistent Nephrogram - Ibrahim, Muhammad Imran; Qayyum, Abdul; Khan, Asad; ., Ayesha; ., Asma; Ali, Zeeshan; ., Shahid (Pakistan Armed Forces Medical Journal, 2015)
INTRODUCTION Retention of administered intravenous contrast for a prolonged period is termed dense persistent Nephrogram. None of the previously mentioned differentials ever included Retro-aortic left renal vein (RLRV) as a cause of unilateral dense persistent nephrogram. First case of its kind is presented here which presented as diagnostic dilemma and eventually turned out to be a normal variant.